2020
DOI: 10.1039/d0cy00379d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the oxidation of copper(i) species during NH3-SCR over Cu-CHA zeolites: a DFT study

Abstract: DFT calculations suggest that Cu(i) oxidation with O2 as the sole oxidant plays a major role in the oxidation half cycle of standard NH3-SCR over Cu-CHA zeolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
6
23
0
Order By: Relevance
“…Based also on previous detailed mechanism studies by Bendrich et al, systems with different ways of partial hydratized dimer were proposed [ 44 ]. The re-oxidation step for copper centers, presented in detail in the literature [ 45 ], is not discussed here; instead, we concentrated on reactions barriers for deNOx in the Cu–O–Zn dimer.…”
Section: Resultsmentioning
confidence: 99%
“…Based also on previous detailed mechanism studies by Bendrich et al, systems with different ways of partial hydratized dimer were proposed [ 44 ]. The re-oxidation step for copper centers, presented in detail in the literature [ 45 ], is not discussed here; instead, we concentrated on reactions barriers for deNOx in the Cu–O–Zn dimer.…”
Section: Resultsmentioning
confidence: 99%
“…† Note that previous studies only considered the per-site to place the two [Cu I (NH 3 ) 2 ] + species. 35,58 It is found that the INT1 structures with the persite are over 50 kJ mol −1 higher in energy compared to those with the para-site. The following INT2 and INT4 structures also have the same preference for the para-site.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…The reoxidation step, requiring activation of O 2 by Cu I ions, is crucial in the NH 3 -SCR reaction cycle, and is vigorously debated in the literature. [21][22][23][24][25][26][27][28][29] The current understanding is that Cu-pair formation, facilitated by mobile Cu I (NH 3 ) 2 complexes, makes the O 2 activation possible, 25,26,30 with the formation of side-on m-Z 2 ,Z 2 -peroxo diamino dicopper(II) complexes. 16,31 This mechanism is proposed for the reaction at low temperatures (r200 1C), where the NH 3 molecule is able to solvate and mobilize Cu II and Cu I ions.…”
Section: Introductionmentioning
confidence: 99%
“…8,25,[32][33][34][35][36] NH 3 -Solvated Cu pairs have also been proposed to be catalytically relevant in the reduction half-cycle. 19,20 Some aspects are still under debate in the oxidation half cycle regarding the role of NO in mediating the activation of O 2 , [22][23][24]29 and which is the structure of the formed intermediates relevant for the catalytic cycle. 18,19,27,28,[37][38][39][40][41] Cu-(NQO)-NH 2 (copper nitrosamine) species, postulated for both the reduction and oxidation half cycles, 18,39 have been recently detected using transient modulation excitation spectroscopic experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation